Penerapan Model Pembelajaran Discovery Lerning untuk Meningkatkan Hasil Belajar Siswa dalam Mata Pelajaran Desain Kemasan Kelas XI Kuliner 4 SMKN 6 Surabaya - Agung Marta Prayoga; Diana Evawati; Mirna Qurrotun Nabilah; Widi Rimastuti; Juni Weningdyah (DIAJAR: Jurnal Pendidikan dan Pembelajaran, 2025)
Packaging design is an essential competency for Culinary Vocational High School students in line with the growth of the packaging industry in Indonesia. This research aims to improve student learning outcomes in the Creative Vocational Project subject focusing on packaging design elements through the implementation of the Discovery Learning model. This Classroom Action Research was conducted in class XI Culinary 4 at SMKN 6 Surabaya with 36 students as subjects. The research was designed in two cycles, each consisting of planning, implementation, observation, and reflection phases. Data were collected through observations of learning activities and student activities, as well as cognitive learning outcome tests. The results showed a significant improvement in learning activities from 72% (sufficient category) in cycle I to 84% (good category) in cycle II. Student activities also increased from 79% (sufficient category) to 81.6% (good category). The most significant improvement was seen in cognitive learning outcomes with the percentage of student mastery increasing from 72.2% in cycle I to 86.1% in cycle II, with the average score increasing from 77.6 to 85.6. Providing stronger motivation and more effective classroom management in cycle II contributed to improved learning outcomes. The implementation of the Discovery Learning model proved effective in enhancing students' conceptual understanding and practical skills in packaging design, while also developing critical thinking skills and creativity relevant to industry demands.